The Early Events That Initiate β-Amyloid Aggregation in Alzheimer’s Disease - Zhang, Xingyu; Fu, Zhihui; Meng, Lanxia; He, Mingyang; Zhang, Zhentao (Frontiers in Aging Neuroscience, 2018)
Alzheimer's disease (AD) is characterized by the development of amyloid plaques and neurofibrillary tangles consisting of aggregated β-amyloid (Aβ) and tau, respectively. The amyloid hypothesis has been the predominant framework for research in AD for over two decades. According to this hypothesis, the accumulation of Aβ in the brain is the primary factor initiating the pathogenesis of AD. However, it remains elusive what factors initiate Aβ aggregation. Studies demonstrate that AD has multiple causes, including genetic and environmental factors. Furthermore, genetic factors, many age-related events, and pathological conditions such as diabetes, traumatic brain injury, and aberrant microbiota also affect the aggregation of Aβ. Here we provide an overview of the age-related early events and other pathological processes that precede Aβ aggregation.